The science of sound : pitch, volume, music, and noise : with hands-on science activities for kids - Diehn, Andi ("Build it yourself" series., 2025)
"The Science of Sound: Pitch, Volume, Music, and Noise with Hands-On Science Activities for Kids is a symphony of learning as readers ages 8 to 11 discover how to identify the sounds around them and pinpoint how they're formed and where they travel from. From splashy puddles to crunchy leaves to barking dogs to a strummed guitar, sound is all around us. For most people, sound plays a major role in their experience of the world. Discover how scientists use sound to map the ocean floor and investigate climate change. Learn how sound exists inside the human body. Examine how sound travels, what a sound wave is, and how the human ear works! In this book, kids have fun learning about sound as a sensation and as a tool of communication--and not just for humans. Hands-on STEM activities, entertaining illustrations, essential questions, text-to-world connections, fascinating sidebars, and links to online resources and videos all make some noise for learning! Additional materials include a glossary, a list of media for further learning, a selected bibliography, and index. Aligns with Common Core state standards and Next Generation Science Standards."--